Adaptation of Xiengtong-Kili Villagers of Luang Prabang Heritage, Luang Prabang Province After Becoming a World Heritage City - CHANHDALATH, Siwath; JUN, Mei; SENEDUANGDETH, Dexanourath (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
This research examines the social and cultural adaptation of the villagers of Xiengthong-Kili, Luang Prabang, and Luang Prabang after Luang Prabang became a World Heritage City. The purpose of this research was to study the social and cultural adaptation of the villagers of Xiengthong-Kili Village. Luang Prabang District, Luang Prabang Province After Luang Prabang became a world heritage city, In this research, qualitative and quantitative research methods were used as the main guidelines. The main methods for finding truth and using two main methods of data collection were questionnaires, interviews, and observations. Data analysis was descriptive analysis, interpretation, and averaging in SPSS. The results showed that social and cultural adaptation had improved the quality of life of the Xienngthong-Kili villagers. Due to higher incomes to meet the needs of the people themselves and other things that make quality, of a better life from the development of infrastructure from the government to the village, relationships between people in the community are getting better and more harmonious. In addition to having a good relationship with each other within the village, there is still a good relationship with people outside the village. Various traditional festivals of the local people are still cherished as ever; some traditions have been revived to accommodate tourism, and traditional festivals have become a tourist activity each season.